Separation of Emulsifiable Oil from a Flotation Solution by Surface Tension Control - A.M.A. Omar (Adsorption Science & Technology)
The oil flotation behaviour of emulsifiable oil was studied using N -octyl- N -benzyl- N -methylglycine (OBM) as the collector and heavy alkylate naphthalene sulphonates (HNS) as the de-emulsifier. The study showed that the surface tension has an effect on oil recovery. The interfacial tension at the air/water interface was controlled by the use of an alcohol such as ethanol, n-propanol and n-butanol and compared with the collector when used alone in froth flotation. The adsorption of the collector from the aqueous solution was investigated by measuring the surface tension as a function of concentration at different temperatures. Surface properties, in particular the critical micelle concentration (CMC), the effectiveness of surface tension reduction (Π CMC ), efficiency (P C20 ), the maximum surface excess (Γ max ) and the minimum surface area (A min ), were measured at temperatures of 25, 35 and 45°C, respectively. The results were discussed in terms of the adsorption isotherm and surface properties of the collectors at the solution/air interface.